(untitled) (Natura Neotropicalis, 2019)
IRIGOYEN, A.; G. TROBBIANI; M. CASALINUOVO; M. ALONSO et al., 2018. Peces y pesca deportiva argentina, Mar y Patagonia. IRIGOYEN, A.; G. TROBBIANI; M. CASALINUOVO; M. ALONSO (eds.). Remitente Patagonia, Trelew, Chubut, Argentina, 272 pp.